Analisis Perlakuan Pajak Penghasilan Pasal 21 Karyawan Atas Pemberian Natura dan/atau Kenikmatan pada PT X di Surabaya - Ghayatul Fikriya; Tjandra Wasesa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the treatment of Income Tax Article 21 (PPh 21) on the provision of benefits in kind and/or facilities (natura dan kenikmatan) to employees at PT X in Surabaya. The research background arises from the company’s practice of recording housing and sports facilities as operational expenses, while according to tax regulations, part of these facilities should be considered taxable income. This study employs a qualitative method with a case study approach. Data were collected through interviews, observation, and documentation of salary reports, PPh 21 recapitulation, and the company’s 2024 tax records. The findings reveal that PT X has not included benefits in kind and/or facilities in its PPh 21 calculations. Individual housing facilities exceeding IDR 2,000,000 per month and golf sports facilities should be treated as employees’ taxable income. The study concludes that the company’s tax treatment does not comply with Regulation of the Minister of Finance (PMK) No. 66 of 2023, requiring adjustments to ensure proper PPh 21 calculation.